CNI 브라운백세미나-뻐꾸기탁란(이진원) - 이진원 (충남연구원, 2015)
O CNI 브라운백세미나-뻐꾸기탁란 Avian brood parasitism in macroecology •Avian brood parasitism and niche evolution •Avian brood parasitism as an environmental indicator •Climate change and avian brood parasitism Searching for host species in Korea ▷Determining current state ▷Suggesting future direction - 이후 생략
Keywords: 뻐꾸기; 탁란